Ein Echo aus der südfranzösischen Diaspora: Briefe an Br. Duvernoy in Zeist (1766) - Gembicki, Dieter (Unitas Fratrum, 2018)
The Moravians' little-known diaspora work in the South of France occurred in difficult circumstances and lasted for half a century. It is fortunate that the letters sent by the Moravian Pierre-Charles Duvernoy to Zeist in 1763-1764 have survived, since they shed an unusually bright light on hardships and joys among the 'Awakened'. All of them seek their faith, affirmation and reassurance. For this conduct, some are punished: a banker's wife from Lyon, for example, even reports having been disinherited. Others strive for their identity: a sister in Bordeaux orders authentic shoes from Zeist, a businessman portraits of Zinzendorf and his son for his parlour ... What they all seek is a feeling of fellowship and belonging. Thanks to this intensive correspondence, all the brethren and sisters in the diaspora understand themselves to be, so to speak, a great family. Death especially they experience 'together', i. e., as far as one can tell from the sources, as a moment of fellowship. This experience is doubtless one of the ways in which the Moravians were exceptional in France before the Revolution.